Hubungan Kadar Kolesterol dengan Hipertensi pada Penderita Penyakit Ginjal Kronik di RSUD Dr. Moewardi - Hasliani, Dian, Dr. Suryo Aribowo Taroeno, M.Kes., Sp.P.D. (KHOM) (2017)
Background: Hypertension is the leading cause of death that was ranked third after stroke and tuberculosis, which reached 6.7% of deaths in all age groups in Indonesia. Had a lot of people have hypertension without knowing for years. Therefore hypertension is referred to as the silent killer. The prevalence of risk factors for hypertension is higher among patients with chronic renal failure and will increase with the severity of chronic kidney disease. Objective: This study aims to determine the relationship of cholesterol levels and hypertension in patients with chronic kidney disease at the Hospital Dr Moewardi Surakarta. This study uses an observational analytic design with cross sectional approach using secondary data obtained from medical records. The study design was used to study the relationship between cholesterol levels and hypertension in chronic kidney disease. Methods: From the analysis using Chi-square test there is a significant correlation between cholesterol levels and hypertension in patients with chronic kidney disease. With a p-value of 0.001 (p <0.005). Based on the results of this study concluded that there is a relationship with hypertension cholesterol levels in patients with chronic kidney disease at the Hospital Dr. Moewardi Surakarta. Resulth: From the analysis using Chi-square test there is a significant correlation between cholesterol levels and hypertension in patients with chronic kidney disease. With a p-value of 0.001 (p <0.005). Based on the results of this study concluded that there is a relationship with hypertension cholesterol levels in patients with chronic kidney disease at the Hospital Dr. Moewardi Surakarta. Conclusion: There is a relationship cholesterol level with hypertension in patients on chronic kidney disease at the hospital Dr. Moewardi Surakarta.